SUGARCANE PRODUCTIVITY AND GASEOUS EXCHANGES ARE NOT AFFECTED BY POTASSIUM FERTILIZATION IN HIGH K CONTENT SOIL - da Rocha, Igor Tenório Marinho; da Silva, Anibia Vicente; Simões Neto, Djalma Euzébio; de Oliveira, Alexandre Campelo; de Souza, Edivan Rodrigues; de Oliveira, Emídio Cantídio Almeida; Freire, Maria Betânia Galvão dos Santos; Freire, Fernando José (REVISTA DE AGRICULTURA, 2022)
This study aimed to evaluate the effect of K2O doses, as KCl, on physiological aspects and agricultural productivity of sugarcane in rainfed cultivation. The experimental design was in randomized blocks in a factorial arrangement (6x2) with 4 replications, with six K2O rates (0, 25, 50, 100, 200 and 250 kg ha-1) and two sugarcane varieties (RB92579 and RB962962). K2O rates did not positively affected physiological characteristics and productivity of the sugarcane varieties. The productivity of the RB962962 variety was higher than that of the RB92579. The variety RB962962 had lower transpiration and stomatal conductance than the variety RB92579. Potassium fertilizers application is not recommended in soils with high soil exchangeable content, above 0.24 cmolc dm-3, as it does not result in increased productivity or improved gas exchange characteristics in sugarcane.